Marine Resource Utilization and Nutrition Education to Prevent Anemia in Tuban - Purnama Sari, Dwi Kurnia; qoyimah, ilmiatus (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Anemia in adolescent girls is a major public health issue in Indonesia and has been identified as one of the contributing factors to stunting. This problem is especially urgent in coastal areas, where despite the abundance of fish as a source of iron and protein, dietary habits often fail to optimize their potential benefits. The aim of this community service program was to enhance knowledge and awareness regarding anemia prevention through nutrition education and fish processing demonstrations targeted at adolescent girls in Tuban’s coastal region. Participants were recruited from five villages and involved in a series of interactive sessions that combined lectures on nutrition and anemia with hands-on demonstrations of simple and locally adapted fish-based recipes. The program was evaluated through pre-test and post-test assessments to measure knowledge improvement. Findings revealed a clear increase in participants’ understanding of anemia, its link to stunting, and the role of fish consumption in maintaining health. The interactive approach encouraged active participation and was effective in fostering positive changes in attitudes and daily dietary practices. In conclusion, integrating nutrition education with practical demonstrations utilizing marine resources is an effective strategy to prevent anemia among adolescent girls in coastal communities. This approach highlights the importance of community-based interventions that are culturally appropriate and resource-based in addressing nutritional challenges.